2018
DOI: 10.1186/s13007-018-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and quantification of grain anthocyanins in purple pericarp × blue aleurone wheat crosses by high-performance thin-layer chromatography and densitometry

Abstract: BackgroundAnthocyanins are abundant secondary metabolites responsible for most blue to blue-black, and red to purple colors of various plant organs. In wheat grains, anthocyanins are accumulated in the pericarp and/or aleurone layer. Anthocyanin pigmented wheat grains can be processed into functional foods with potential health benefits due to the antioxidant properties of the anthocyanins. The grain anthocyanin content can be increased by pyramidizing the different genes responsible for the accumulation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Liu et al found remarkable antioxidant effects from purple wheat rather than red, yellow, and white wheat, and the outstanding activity was correlated with higher anthocyanin content, such as cyanidin 3-glucoside ( 4 ). Since the antioxidant colorant is expressed in the outer layer of wheat grain ( 4 6 ), it further encourages the consumption of bran and whole grain.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found remarkable antioxidant effects from purple wheat rather than red, yellow, and white wheat, and the outstanding activity was correlated with higher anthocyanin content, such as cyanidin 3-glucoside ( 4 ). Since the antioxidant colorant is expressed in the outer layer of wheat grain ( 4 6 ), it further encourages the consumption of bran and whole grain.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged high humidity and temperature have been found to have an effect on grain discolouration [6], therefore, it is probable that the conditions in the glasshouse of this study did not favour red smudge development. The incidence of red smudge may also be related to the grain type, since pigmented phenolic compounds such as catechins, proanthocyanidins and anthocyanins accumulate in the grain coat [21,22] resulting in coloured grain. White grain wheats are only produced in Australia; however, the evaluation of other varieties, including the red grain wheats produced in America and Europe, would be of interest for further work.…”
Section: Discussionmentioning
confidence: 99%
“…It was also developed in Japan and later transferred to the Indian germplasm ( 4 ). Black wheat development has been reported in Austria ( 30 ) and Ukraine ( 31 ). It appeared black (deep purple hue) as it had color in both pericarps and aleurone layers ( Figure 1 ) and has the same genetics as purple and blue wheat.…”
Section: Origin and Genetics Of Anthocyanin Accumulation In Colored W...mentioning
confidence: 99%